MicroRNAs in Microglia: How do MicroRNAs Affect Activation, Inflammation, Polarization of Microglia and Mediate the Interaction Between Microglia and Glioma? - Guo, Yawei; Hong, Wenming; Wang, Xinming; Zhang, Pengying; Körner, Heinrich; Tu, Jiajie; Wei, Wei (Frontiers in Molecular Neuroscience, 2019)
The essential roles of microglia in maintaining homeostasis in the healthy brain and contributing to neuropathology are well documented. Emerging evidence suggests that epigenetic modulation regulates microglial behavior in both physiological and pathological conditions. MicroRNAs (miRNAs) are short, non-coding epigenetic regulators that repress target gene expression mostly via binding to 3’-untranslated region (3'-UTR) of mRNA in a Dicer-dependent manner. Dysregulation of certain miRNAs can contribute to microglial hyper-activation, persistent neuroinflammation, and abnormal macrophage polarization in the brain. These abnormal conditions can support the pathogenesis of neurological disorders such as glioma, Alzheimer’s disease, amyotrophic lateral sclerosis, stroke, ischemia, and spinal cord injury. However, the roles of miRNAs in microglia in health and neurological disease have not been systematically summarized. This review will firstly report the role of Dicer, a key endoribonulease that is responsible for most miRNA biogenesis in microglia. Secondly, we will focus on recent research about the function of miRNAs in activation, inflammation and polarization of microglia, respectively. In addition, potential crosstalk between microglia and glioma cells via miRNAs will be discussed in this part. Finally, the role of two essential miRNAs, miR-124, and miR-155, in microglia will be highlighted.